The Development of RADEC (Read, Answer, Discuss, Explain, and Create) Based E-LKPD Using Classwork.com on Redox and Electrochemistry Material - Febriesta, Wargi; Lenny Anwar S; Abdullah (The Future of Education Journal, 2026)
This research is motivated by the low engagement of students and the limited interactive teaching materials in chemistry learning, especially on abstract and complex topics such as redox and electrochemistry. The aim of this study is to develop an Electronic Student Worksheet (E-LKPD) based on the RADEC (Read, Answer, Discuss, Explain, and Create) learning model using the Classwork.com platform and to determine the validity level and user responses to the developed E-LKPD. This research is a Research and Development (R&D) study using the 4D model, which includes the define, design, and development stages. The research subjects consisted of two content validators, one media validator, two chemistry teachers, and 20 twelfth-grade high school students. Data were collected using validation questionnaires and user response questionnaires with a Likert scale, then analyzed descriptively and quantitatively. The results show that the E-LKPD received a content validation percentage of 97.4% and a media validation percentage of 100%, both categorized as very valid. Teacher responses to the E-LKPD yielded a percentage of 87.5%, categorized as very good, while student responses had an average percentage of 92.94%, also categorized as very good. Based on these results, it can be concluded that the RADEC-based E-LKPD using Classwork.com for the electrochemistry material is valid and practical for use in high school chemistry learning.